Metode Resource Based Learning untuk Meningkatkan Motivasi Belajar Fiqih Siswa Kelas V Madrasah Ibtidaiyah Al Ishlah Yayasan Zunnuroin Pulau Tengah - Atila Khalifah; Rusmanto Rusmanto (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This thesis is motivated by the observed issue that students in Class V at Madrasah Ibtidaiyah Al Ishlah have low learning motivation during the teaching and learning process. Therefore, to attract students’ attention and enhance their motivation in learning Fiqih, the Resource-Based Learning (RBL) method can be applied. The purpose of this research is to identify the improvement in students’ learning motivation through the implementation of the Resource-Based Learning (RBL) method in Fiqih learning at Madrasah Ibtidaiyah Al Ishlah.This research is a Classroom Action Research (CAR). The types of data used in this study are quantitative and qualitative data. The sources of data required and used include interviews with informants, documentation, and the teaching and learning process. Data collection instruments include observation, interviews, tests, and documentation.The results of this study indicate that the research process from the first cycle to the second cycle was carried out well. Students’ learning motivation in the Fiqih subject through the Resource-Based Learning model significantly improved. This is evident from the teaching and learning activities in the classroom. In the pre-cycle, the score showed 35.9%. This increased to 74.75% in the first cycle and further to 83% in the second cycle. Although the pre-cycle results did not meet the expected criteria, and the first cycle showed improvement but still fell short, the second cycle demonstrated significant improvement and met the established criteria.This indicates that the use of the Resource-Based Learning method in Class v MI Al ishlah can apparently increase atudents learning motivasi in fiqih subjects.